Dataset from:Combination antiretroviral therapy (Atripla) in diabetes exacerbates diabetogenic effects on hippocampal microstructure, neurogenesis, and cytokines levels in male Sprague Dawley rats - Johnson, Jaclyn Asouzu; Ndou, Robert; Mbajiorgu, Ejikeme F (My University, 2021)
Combination antiretroviral therapy (cART) has effectively reduced the scourge of HIV infection. However, with the increasing incidence of diabetes, HIV/AIDS-diabetes co-morbidity has become prevalent in society with chronic cART therapy in diabetes. Therefore, this study investigated the neuronal effects of cART and type two diabetes (T2D) on the levels of cytokines, lipid peroxidation, histomorphology and neurogenesis in the hippocampus. Adult male Sprague Dawley rats were divided into 4 groups: DB (diabetic rats), DAV (diabetic rats treated with cART (efavirenz, emtricitabine, and tenofovir), AV (normal rats treated with cART) and NC group (with no treatment). Following ninety days treatment, the rats were terminated, and the brains excised. Immunoassay (IL-1α, IL-6, TNFα and MDA), immunohistochemical (Ki67 and DCX) and Cresyl violet histomorphology analysis were carried out on brain homogenate and sections, respectively. In comparison to the control, the results show that cART significantly elevated IL-1α, IL-6, TNFα and MDA levels but had no effect on FBG, NFBG and glucose tolerance. While DB and DAV significantly reduced body weight ,glucose tolerance, IL-1α, IL-6, TNFα and MDA levels. Hippocampal neuronal density was reduced in cART (in DG), diabetes group (in CA1 and DG only) and in cART therapy in diabetes (in all hippocampal regions). Also, the expression of Ki67 and DCX were reduced in diabetic both the DB and DAV groups. Furthermore, increase in DG neuronal nuclei of DB and DAV is significantly corelated to FBG, NFBG, AUC, and inversely corelated to neuronal density and neurogenesis. These findings indicate that cART treatment in diabetes maintains diabetic effects of impairing cytokine and inducing oxidative stress, but it cumulates in exacerbated neurotoxicity by significantly reducing DCX compared to DB and reduction in the density and nuclei size of CA3 hippocampal neurons, unlike cART or diabetes independently.
Body weight, DCX, Fasting blood, iL1, Ki67, MDA, Mean density, Non-fasting blood, Oral Glucose area under curve, TNF Alpha.
This data is closed as it is being submitted for publication Its been deposited on REDCAP project PID 15711 and is available after publication on request. The rights to the data are jointly held Combination antiretroviral therapy (Atripla) in diabetes exacerbates diabetogenic effects on hippocampal microstructure, neurogenesis, and cytokines levels in male Sprague Dawley rats Body weight: Mean body of 6 animals each per group; four treatment groups. Groups: NC, Controls; AV, cART only; DB, Diabetic; DAV, diabetic with cART. Fasting_NonFasting_Oral Glucose test: Mean fasting blood glucose test of 6 animals each per group; four treatment groups. Groups: NC, Controls; AV, cART only; DB, Diabetic; DAV, diabetic with cART. Mean non-fasting blood glucose test of 6 animals each per group; four treatment groups. Groups: NC, Controls; AV, cART only; DB, Diabetic; DAV, diabetic with cART. Mean Oral Glucose Tolerance Test (OGTT) of 6 animals each per group; four treatment groups. Groups: NC, Controls; AV, cART only; DB, Diabetic; DAV, diabetic with cART. (Reading of blood glucose at 0 minutes, 15 minutes, 30 minutes, 60 minutes, and 120 minutes) Mean Area Under Curve (AUC) of the OGTT for 6 animals each per group; four treatment groups. Groups: NC, Controls; AV, cART only; DB, Diabetic; DAV, diabetic with cART. Nissl Histology_neuronal nuclei and number: Count and mean of neuronal cell density at three hippocampal regions [CA1, CA3, DG (dentate gyrus)]. mean CA1 density, meanCA3 density, meanDG density Count and mean of neuronal nuclei area at three hippocampal regions [CA1, CA3, DG (dentate gyrus)]. mean CA1nuclei area, mean CA3nuclei area, meanDgnuclei area Two counts for CA1 and CA3 density per section Five counts for DG density per section Three measurements for CA1, CA3, DG neuronal nuclei per section 6 sections per animal, 6 animals each per group; four treatment groups. Groups: NC, Controls; AV, cART only; DB, Diabetic; DAV, diabetic with cART. Immunohistochemistry DCX_Ki67: Count and mean of cells expressing DCX and Ki67 DCX; 4 sections per animal, 6 animals each per group; four treatment groups. Groups: NC, Controls; AV, cART only; DB, Diabetic; DAV, diabetic with cART. Ki67; 4 sections per animal, 6 animals each per group; four treatment groups. Groups: NC, Controls; AV, cART only; DB, Diabetic; DAV, diabetic with cART. Cytokines_MDA: Concentration and means of pro-inflammatory cytokines IL-1α, IL-6, TNFα and oxidative stress markers MDA. Mean concentration of cytokines and MDA in 4 animals each per group: four treatment groups. Groups: NC, Controls; AV, cART only; DB, Diabetic; DAV, diabetic with cART
Keywords: diabetes, antiretroviral, cytokines, neurogenesis, hippocampus microstructure; Blood Glucose; Diabetes; Antiretroviral; Cytokines; Neurogenesis; Hippocampus microstructure; Blood Glucose; Anti-HIV-Agents; Interferons; Neuronal outgrowth; Entorhinal Cortex